Degradation behaviors and cytocompatibility of Mg/β‐tricalcium phosphate composites produced by spark plasma sintering. Issue 7 (1st February 2019) - Narita, Kai; Tian, Qiaomu; Johnson, Ian; Zhang, Chaoxing; Kobayashi, Equo; Liu, Huinan
Abstract: Magnesium (Mg)‐based materials have shown great potentials for bioresorbable implant applications. Previous studies showed that Mg with 10 and 20 vol % β‐tricalcium phosphate (β‐TCP) composites produced by spark plasma sintering, improved mechanical properties when compared with pure Mg. The objectives of this study were to evaluate the degradation behaviors of Mg/10% β‐TCP and Mg/20% β‐TCP composites in revised stimulated body fluid (rSBF), and to determine their cytocompatibility with bone marrow derived mesenchymal stem cells (BMSCs) using the direct culture method. During the 11 days of immersion in rSBF, Mg/β‐TCP composites showed different degradation behaviors at different immersion periods, that is, the initial stage (0–1 hr), the mid‐term stage (1 hr to 2 days), and the long‐term stage (2−11 days). The counter effects of mass loss due to microgalvanic corrosion and mass gain due to deposition of Ca‐P containing layers resulted in slower Mg 2+ ion release for Mg/20% β‐TCP than Mg/10% β‐TCP in the mid‐term, but eventually 16% mass loss for Mg/20% β‐TCP and 10% mass loss for Mg/10% β‐TCP after 11 days of immersion. The in vitro studies with BMSCs showed the highest cell adhesion density (i.e., 68% of seeding density) on the plate surrounding the Mg/10% β‐TCP sample, that is, under the indirect contact condition of direct culture. The β‐TCP showed a positive effect on direct adhesion of BMSCs on the surface of Mg/β‐TCP composites. This study elucidated the degradation behaviors and the cytocompatibility of Mg/β‐TCP composites in vitro; and, further studies on Mg/ceramic composites are needed to determine their potential for clinical applications. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 2238–2253, 2019.